Socio-Demographic and Economic factors associated with hypertension among Men in India - Ganapati Sabhahit; Rajeshwari A Biradar; Prasad Jung Bahadur; Sadashiva Hegde; Rachana R Shetty; Vishaka S Shetty; Rasika Mahagaonkar (Asia Pacific Journal of Health Management)
Background: The leading risk factor for cardiovascular disease, Hypertension, is becoming more prevalent worldwide and is especially prevalent in low- and middle-income nations (LMICs) like India.